Arouse the Creativity of a Generation of Millenial Doctrines with the Media Learning Physics and Innovative Eco-Friendly - Nurhidayati, Nurhidayati; Fauzia, Syifa; Maknun, Al Lu’lu Ul (Proceeding International Conference on Science and Engineering, 2019)
Learning media is an auxiliary tool effectively which can be used by teachers to achieve the desired goals. Learning media usage in the process of teaching and learning can evoke desire and renewed interest, evoking motivation and stimulation of learning activities, even bringing the influences of Psychology against the students. Learning Media research already done by observing the learning achievements before and after using the media. On the research of Alamsyah Noerseelha with the title of "research learning media use power point" in SMK N 1 learning achievements acquired Sumedang of 68.57 before using media and 80.00 after using media. With the name and title of the same study at Junior High School N 1 Cimanggung obtained amounted to 61.90 before using media and 80.95 after using media. and in Junior High School N 1 Pamulihan of 67.74 before using media and 83.33 after using media. The main factors that can enhance the learning achievements and arouse the creativity of learners, namely the media and education. While the hallmark of a generation of millennial doctrines which tend to be deeply affected by the technology make it quickly bored with the monotonous thing. To address the authors offer solutions in the form of ideas where teachers use the media learning and learners practice to create a new media that he apply the learning of physics that they already get in College. Because of a growing country is the question "want to be tomorrow what?" while the question of an advanced country that "tomorrow would like for what?". The aim to arouse the creativity of a generation of millennial doctrines created new things by making it interested in the learning media that already exists.